Electromobility and the Environment in the Czech Republic - Turek Michal; Kalupová Blanka; Cempírek Václav; Tůmová Kateřina; Abramović Borna (Logi, 2024)
Background: Reducing the carbon footprint in transport through the introduction of electromobility is stipulated by the European legal framework. The shift to electric vehicles requires idenfining the types of emissions from combustion engines that will be eliminated through electromobility. In addition to environmental benefits, another advantage of electromobility will is the reduction of noise pollution. Methods: From a technical point of view, it is necessary to assess the characteristics of these vehicles by focusing on the tire design, which a significantly influences their performance, and to examine the impact of policy proposals and technical advancements on the number of electric vehicles registrations and their development over a given period. Results: The paper confirms that legislative developments and improvements in the technical characteristics of electric cars are driving an upward trend in the number of registered clean vehicles, which reduces their envirimental impact. Conclusion: The authors of the article conclude that, despite higher investment and operating costs, the operation of electric cars, when supported by appropriate forms of support, represents an opportunity to reduce the carbon footprint in transport.